Factor VIII haplotypes frequencies in Tunisian hemophiliacs A - Meddeb Balkis; Zahra Kaouther; Jlizi Asma; Belhedi Nejla; Elmahmoudi Hejer; Elgaaied Amel; Gouider Emna (BMC, 2011)
Abstract Background The development of inhibitors against factor 8 (F8) is the most serious complication of replacement therapy with F8 in children with severe hemophilia. It was suggested that mismatched F8 replacement therapy may be a risk factor for the development of anti-factor F8 alloantibodies. Recently four single nucleotide polymorphisms (SNPs) encoding six distinct haplotypes, designated H1 through H6, were studied in different populations. Two SNPs are components of the A2 and C2 immunodominant-inhibitor epitopes. The aim of this study is to determine the different types of haplotypes in relation with inhibitors developments and their frequencies in our Tunisian hemophiliac population. Materials and methods 95/116 Tunisian patients with hemophilia A undergoing treatment at Hemophilia Treatment Center, Aziza Othmana hospital, participate in this study. Among them only six patients develop inhibitors. The four SNPs were amplified and sequenced. Results and Discussion In a total of 77 patients, we identified the H1, H2, H3 and the infrequent H5 haplotypes. The H1 and H2 haplotypes, which have the same amino acid sequence in the recombinant F8 molecules used clinically, are the most represented with the frequency of 0.763 and 0.157 respectively. This distribution is almost similar to that of Caucasians in which the frequencies are respectively 0.926 and 0.074, whereas it is 0.354 and 0.374 among Subsaharians. Four patients with inhibitors studied here have the H1 haplotype. For one patient who has a large deletion including the exon 10 we can't identify his haplotype. Theses frequencies may explain partially the low level of inhibitors in our patients.